Predicting Hydraulic conductivity (k) of tropical soils by using artificial neural network (ANN) - Lim, D.K.H; Kolay, P.K (Universiti Malaysia Sarawak (UNIMAS), 2009)
Hydraulic conductivity of tropical soils is very complex. Several hydraulic conductivity prediction methods have focuses on laboratory and field tests, such as Constant Head Test, Falling Head Test, Ring Infiltrometer, Instantaneous profile method and Test basin. This study demonstrate the comparison between the conventional estimation of k by using Shepard's equation for approximating k and the predicted k from ANN.